Effectiveness of Monetary Policies and Strategies: A Case of Nepal - Sigdel, Bama Dev (Economic Journal of Nepal, 2006)
A well-structured monetary policy can contribute to the fulfillments of the objectives such as full employment, stable price, and economic growth. The initiation of monetary policy in Nepal dates back to 1960s. Since then Nepal Rastra Bank (NRB) has been introducing various form of monetary policies and strategies. NRB Act 2055 paved the way to formulate sound comprehensive monetary policy and strategies by Nepal Rastra Bank. Consequently, NRB has introduced monetary policies since the fiscal year 2002/03. Due to the implementation and favorable impact of such monetary policies and strategies, progress has been witnessed on the process of financial deepening in the economy. Thus, one can draw the conclusion that Nepalese monetary policies introduced in the past have been successful to some extent to drive the economy on the right track curbing inflation, injecting needed money for the economy and thereby maintaining BOP position comfortable. The monetization of a broader range of economic activities and transaction would facilitate financial savings, as would the broadening of the range of flexible saving instruments–all key elements in the process of financial deepening, which is often measured by the rate of broad money to GDP. With more financial deepening enabling house holds to better smooth their consumption which in turn feeds back to a more stable real economy. Economic Journal of Nepal Vol.29(1) 2006 pp.38-53